SINERGITAS PERUBAHAN DATA MAHASISWA PADA PD.DIKTI (Studi Perubahan data Biodata Mahasiswa UINSI Samarinda) - Halim, Muhammad Faisal (Journal of Social Computer and Religiosity (SCORE), 2023)
Many students experience incorrect data on names, student identification numbers, places of birth dates, population identification numbers, and different parents' names. They do not know how to improve the data or the obstacles faced in the process of changing data on the UINSI Samarinda academic information system, while the reporting of higher education academic data is done every semester to the Pd.Dikti of the Ministry of Education and Culture. This research is a type of qualitative research, using qualitative descriptive methods with a naturalistic approach. This research is field research that concerns the description and depiction of data change services in the UINSI Samarinda academic information system, which was observed over a period of time. The results obtained from the research on data changes in the academic information system of the State Islamic Institute (UINSI) Samarinda The role of students who experience data changes in completing supporting documents is very important. By coordinating with the Rectorate, we were able to follow up on the correct data and propose changes to the data on the PD-Forlap application by the Information Technology Unit and the UINSI Samarinda Database.